The Role of School Principals in the Implementation of the Minister of Religion Number 183 and Number 184 of 2019: curriculum, the role of the principal, implementation - Muhamad Khoirur Roziqin; Siti Lailatul Mahfudhoh (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
The newly implemented Curriculum of the Minister of Religion Number 183 and Number 184 of 2019 can encourage the education and learning process in Islamic schools to become more dynamic, creative, and innovative. Curriculum changes make it clear that learning is a shared responsibility between teachers, principals, and the education board. In implementing the curriculum, the principal plays an important role because the principal is responsible for the school he leads and is required to develop the professionalism of teachers and education personnel. The failure in implementing this curriculum is due to the lack of knowledge, skills, and abilities of teachers in carrying out their duties that must be carried out. These conditions indicate that the functioning of the curriculum lies in its implementation in schools. Therefore, this study aims to obtain empirical evidence regarding the Principal's Role in the Implementation of the Curriculum of the Decree of the Minister of Religion Number 183 and Number 184 at Bahrul Ulum Tambakberas High Islamic School Jombang. This study was used to determine how important and influential the role of the principal is to establish a religious culture as an effort to improve student discipline, and the results of this study can add to the literature and can be used as reference material for further research. The research method used is descriptive qualitative analysis. The data collection used is interviews, observation and documentation. Data collection in the field was carried out in 2021. The results showed that the Bahrul Ulum Madrasah had implemented the curriculum of the Minister of Religion Decree No. 183 and No. 184 in this year's teaching